Moguls the lives and times of Hollywood film pioneers Nicholas and Joseph Schenck - Benson, Michael 1962-; Singer, Craig (Citadel Press, Kensington Publishing Corp., 2024)
"Groundbreaking pioneers of the Hollywood Dream Factory, Joseph and Nicholas Schenck may not have been household names like the Warner brothers or Louis B. Mayer, but they were infinitely more powerful, influential--and ruthless. A pair of Russian immigrants with giant ambitions, the Schencks turned their small nickelodeon business in New York's Bowery into a partnership with Loew's movie theaters and a controlling interest in three major studios: MGM, 20th Century Fox, and United Artists. They painted the silver screen silver, laid the foundations for the all-powerful studio system, and ruled a global movie empire from their Gatsby-sized mansions on the East and West coasts. The Schencks had become moguls"--
"Power, scandal, mob, Marilyn, more!"--Cover
Keywords: Schenck, Joseph M. -- 1876-1961; Schenck, Nicholas -- 1880-1969; Metro-Goldwyn-Mayer; Twentieth Century Fox Film Corporation; Filmwirtschaft; Schenck, Joseph M. / 1877-1961; Schenck, Nicholas; Motion picture producers and directors / Biography; Motion picture industry / United States / History / 20th century; Producteurs et réalisateurs de cinéma / Biographies; Cinéma / Industrie / États-Unis / Histoire / 20e siècle; Biographies; Biografie